Respuesta :
x^2 - 12x + ___
take half of ur x term.....ur x term is -12.....half of it is -6.....then square it...
-6^2 = 36 <== this is ur constant
x^2 - 12x + 36
take half of ur x term.....ur x term is -12.....half of it is -6.....then square it...
-6^2 = 36 <== this is ur constant
x^2 - 12x + 36
The missing constant term in the perfect square that starts with [tex]\rm x^2-12[/tex] is 36.
What is the perfect square?
A perfect square is defined as the integer that can be expressed as the square of another integer.
The missing term in the expression will make the expression a perfect square.
The given expression is;
[tex]\rm x^2-12[/tex]
To complete a square, we need to add the square of half of the coefficient of x.
The missing constant is;
[tex]\rm =x^2-12x\\\\ = x^2-12x+36\\\\ = x^2-6x-6x+36\\\\ =x(x-6)-6(x-6)\\\\ =(x-6)(x-6)\\\\=(x-6)^2[/tex]
Hence, the missing constant term in the perfect square that starts with [tex]\rm x^2-12[/tex] is 36.
To know more about perfect square click the link given below.
https://brainly.com/question/16038558
#SPJ3